Optimalisasi Pengetahuan Ibu Terkait Pemberian Vitamin A Pada Balita 6-59 bulan di Kelurahan Gunung Pangilun, Kecamatan Padang Utara - Sari, Putri Permata (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2023)
World Health Organization (WHO), around 190 million children still experience vitamin A deficiency in pre-school children, especially in Southeast Asia and Africa. WHO recommends giving vitamin A supplements regularly, including in Indonesia. Providing vitamin A supplements for children aged 6-59 months has proven to be useful for preventing infections, diseases (such as ARI, measles and diarrhea), increasing body resistance. The aim of this community service is to increase mothers' understanding of giving vitamin A to toddlers. Before providing information, the mother's knowledge about administering vitamin A will be identified through a pre-test. Next, the material is given and the post-test is carried out again. This activity was carried out in Gunung Pangilun sub-district, Padang City on October 15 2023. The target of this activity is mothers who have 38 toddlers. The expected result of this service activity is increased cognitive, affective and psychomotor skills regarding giving vitamin A to toddlers. The method used is education or providing material by distributing leaflets about vitamin A for toddlers. Implementation stages include preparation, implementation and evaluation. The community service team involved are experts in the field of public health who are experienced in their field. The results of the service showed that knowledge and understanding of giving vitamin A increased by 80%. So it is hoped that there will be regular education about giving vitamin A so that the coverage of giving vitamin A is optimal to improve the health status of children under five.